Correlation between Prostatic Volume and International Prostatic Symptom Score in Patients with Benign Prostatic Hyperplasia - Sadiq, Hafsa; Bilal, Rizwan; Shafique, Mobeen; Waqar, Sana; Ghazanfar, Qurat Ul Ain; Azam, Sehrish (Pakistan Armed Forces Medical Journal, 2024)
Objective: To determine the correlation between transabdominal ultrasound prostatic volume and International Prostatic Symptom Score in patients with benign prostatic hyperplasia. Study Design: Cross-sectional study. Place and Duration of Study: Armed Forces Institute of Radiology and Imaging, Rawalpindi Pakistan, from Sep 2020 to Apr 2021. Methodology: Forty five patients were enrolled after taking informed consent. Detailed history was taken and all patients were assessed using the International Prostate Symptom Score. Findings were noted on a predesigned proforma after which all patients were prepared for transabdominal ultrasound in order to achieve bladder volume of at least 50 to 99 ml. Subsequently, transabdominal ultrasound was carried out for determining the volume of the prostate and all findings were subjected to statistical analysis. Results: Mean age of patients was 66.6±9.91 years, with the mean International Prostate Symptom Score being 20.53±9.84 and volume of prostate being 59.56±27.18 cc. Five patients (11.1%) had mild symptoms, 15(33.6%) had moderate and 25(55.6%) had severe symptoms. With regards to volume of prostate, Grade I, II, III and IV was seen in 6(13.3%), 7(15.6%), 20(44.4%) and 12(26.7%) patients respectively. Significant positive correlation was seen between prostatic volume and International Prostate Symptom Score as indicated by an r=0.437 and p=0.003. Conclusion: Transabdominal prostatic volume was found to be significantly correlated with International Prostate Symptom Score, and can be used as an objective assessment of symptoms severity.